The role of social and human capital among nascent entrepreneurs - Davidsson, Per; Honig, Benson (Journal of Business Venturing, 2003)
This study examines nascent entrepreneurship by comparing individuals engaged in nascent activities (n=380) with a control group (n=608), after screening a sample from the general population (n=30,427). The study then follows the developmental process of nascent entrepreneurs for 18 months. Bridging and bonding social capital, consisting of both strong and weak ties, was a robust predictor for nascent entrepreneurs, as well as for advancing through the start-up process. With regard to outcomes like first sale or showing a profit, only one aspect of social capital, viz. being a member of a business network, had a statistically significant positive effect. The study supports human capital in predicting entry into nascent entrepreneurship, but only weakly for carrying the start-up process towards successful completion.